2018
DOI: 10.3892/ol.2018.7993
|View full text |Cite
|
Sign up to set email alerts
|

Loss of expression rather than cytoplasmic mislocalization of RUNX3 predicts worse outcome in non-small cell lung cancer

Abstract: Functional inactivation of human runt-related transcription factor 3 (RUNX3) through mutation or epigenetic silencing has been well-documented in many cancerous entities. In addition to gene mutation and promoter hypermethylation, cytoplasmic mislocalization has emerged as another major manifestation of RUNX3 dysfunction in malignancies including breast, colorectal and gastric cancers. The aim of the present study was to investigate whether patients with non-small cell lung cancer (NSCLC) and different RUNX3 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Our studies identify RUNX3 as a novel target gene of miR-301a in NSCLC cell lines and Kras mutated mice. RUNX3, as a tumor suppressor gene, is frequently inactivated in human cancer cell lines and patient samples [38, 39]. Loss of RUNX3 occurs more frequently in invasive lung adenocarcinoma than in pre-invasive lesions [40].…”
Section: Discussionmentioning
confidence: 99%
“…Our studies identify RUNX3 as a novel target gene of miR-301a in NSCLC cell lines and Kras mutated mice. RUNX3, as a tumor suppressor gene, is frequently inactivated in human cancer cell lines and patient samples [38, 39]. Loss of RUNX3 occurs more frequently in invasive lung adenocarcinoma than in pre-invasive lesions [40].…”
Section: Discussionmentioning
confidence: 99%
“…RUNX3 function as an important transcription factor of the TGF‐β‐mediated signaling pathway. It plays a tumor suppressive role in various human cancers, including oral squamous cell carcinoma, laryngeal carcinoma, breast cancer, lung cancer, HCC, gastric cancer, pancreatic cancer, and colorectal cancer . Notably, Yang et al indicated that the upregulation of RUNX3 after miR‐106b‐5p suppression implying that RUNX3 might be a tumor‐suppressor in retinoblastoma and a target of miR‐106b‐5p.…”
Section: Discussionmentioning
confidence: 99%
“…Hematoxylin-eosin-stained slides from all DLBCL cases were reviewed, non-necrosis areas with the reprensentatively highest tumor cell were selected for tissue microarray (TMA) construction. The TMA was constructed according to a method described previously17, 21, 22. Immunohistochemistry (IHC) studies for a variety of markers were performed on 4 μm TMA sections.…”
Section: Methodsmentioning
confidence: 99%